Sistem Pakar Kerusakan Mesin Kopi Espresso Lamarzocco di Kopi Daripada dengan Metode Forward Chaining - Rizal; Rafi Aulia Akbar; Ahmad Gunawan (Universitas Muhammadiyah Prof. DR. HAMKA, 2024)
Each tool and part contained in a coffee maker has its own level of importance and may not function optimally. This problem often becomes a problem for users or bartenders on duty at work. To overcome this problem, this can be done by someone who has basic knowledge of Lamarzocco coffee makers. However, sometimes these problems also require a high level of expertise from the components so that special technicians are needed to repair them. How to design an expert system application with the forward chaining method to diagnose failures in Lamarzocco coffee machines. In this research the author used the PHP programming language and MySQL database. The research method used by the author is data collection, analysis and object-oriented programming. The program can then be accessed on the website for ease of use, which will then be black box tested with the manager or supervisor of the relevant point of sale. The results of research on the design and application of an expert system using the forward chaining method can diagnose damage to an espresso coffee maker (Lamarzocco coffee maker), this expert system application can be used to assist employees in handling damage to a Lamarzocco espresso machine very well without any problems occurring, and From the results of trials using black box testing on the Lamarzocco coffee machine damage expert system application, we got good results